2011
DOI: 10.1016/j.intimp.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory effect of polysaccharides from Lobophora variegata on zymosan-induced arthritis in rats

Abstract: This study analyzes the action of sulfated polysaccharides, fucans, from algae Lobophora variegata on zymosan-induced arthritis in rats. Groups of fucans, obtained after acetone fractionation (0.3-2.0 volumes), were denominated F0.3, F0.5, F0.8, F1, F1.5, and F2. The results that F1 contained a high yield in relation to other fractionated fucans. Chemical and structure analysis of F1 was performed by nuclear magnetic resonance (NMR) and infrared (IR) spectroscopies. The in vitro antioxidant activities of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 37 publications
1
21
0
2
Order By: Relevance
“…Many in vitro antioxidant assays (DPPH, FRAP, TEAC, NO, and ABTS radical scavenging) have demonstrated antioxidant potential of numerous seaweed polysaccharides (Ngo, Wijesekara, Vo, Van Ta, & Kim, 2011) including sulphated polysaccharides and β-glucans from a variety of seaweeds (Turbinaria conoides, Laminaria japonica, Sargassum fulvellum, and Dictyota mertensii) (Costa et al, 2010;Ngo et al, 2011;Paiva et al, 2011;Wang et al, 2010). Limited research exists linking the antioxidant activity of seaweed extracts in vitro with in vivo studies in human or animal subjects (in particular pigs).…”
Section: Lipid Oxidation In Fresh Ld Musclementioning
confidence: 99%
“…Many in vitro antioxidant assays (DPPH, FRAP, TEAC, NO, and ABTS radical scavenging) have demonstrated antioxidant potential of numerous seaweed polysaccharides (Ngo, Wijesekara, Vo, Van Ta, & Kim, 2011) including sulphated polysaccharides and β-glucans from a variety of seaweeds (Turbinaria conoides, Laminaria japonica, Sargassum fulvellum, and Dictyota mertensii) (Costa et al, 2010;Ngo et al, 2011;Paiva et al, 2011;Wang et al, 2010). Limited research exists linking the antioxidant activity of seaweed extracts in vitro with in vivo studies in human or animal subjects (in particular pigs).…”
Section: Lipid Oxidation In Fresh Ld Musclementioning
confidence: 99%
“…However, the ratio of fucose in WPS and WPS-3 were 25.74% and 32.51%, respectively. It has been revealed that fucose or fucan were received as critical factor in algal polysaccharides bioactivities [26,27]. Therefore, fucose contents in Laminaria japonica polysaccharides might provide some contributions to their bioactivities.…”
Section: Effects Of Polysaccharides On Vsmcs Proliferationmentioning
confidence: 99%
“…The experimental inflammation models utilized revealed that fucans, like heparin, inhibit the leukocyte migration to the inflammation site (55-70%). Earlier studies show that the fucoidan, or fucan, extracted from the brown alga Fucus vesiculosus, inhibits in a dose-dependent manner, but not specifically, the rolling and migration (Yang et al, 1996;Paiva et al, 2011) of leukocytes in processes mediated by molecules of the selectin family. Furthermore, this polymer is also capable of decreasing injury in models of inflammation caused by non-infectious agents (Ostergaard et al, 2000).…”
Section: Measurement Of Nomentioning
confidence: 99%
“…It is a potent inhibitor of leukocyte migration during the infl ammatory response, owing to its interaction with P and L-selectin (Zang et al, 2001;Klintman et al, 2002). Recently, it was revealed that sulfated fucans from the Fucales and Laminariales orders inhibit leukocyte recruitment in an infl ammation model in rats (Cardoso et al, 2010;Paiva et al, 2011). However, there are no reports of leukocyte migration inhibition by fucans from the Dictyotales order.…”
Section: Introductionmentioning
confidence: 99%